State Higher Education Councils in India : Opportunities and Challenges - World Bank Group (Washington, DC, 2014)
One of the pre-requisites of the Rashtriya Uchchatar Shiksha Abhiyan (RUSA) scheme requires that states form a State Higher Education Council (SHEC). This represents a fundamental change in Indian higher education policy, especially in recognition of the role of the states as the unit of planning, and the intent that multiple funding streams to states (Central and State) be aligned with the SHEC planning. However, beyond the RUSA requirements, the scale and complexity of the Indian higher education system require that the states play a more active role in planning and coordinating the system. To carry out this more active role, states must have effective SHEC.